2018
DOI: 10.1007/s10120-018-0858-2
|View full text |Cite
|
Sign up to set email alerts
|

CD44+ cytokeratin-positive tumor cells in blood and bone marrow are associated with poor prognosis of patients with gastric cancer

Abstract: Background The phenotypic heterogeneity of circulating tumor cells (CTC) in peripheral blood and disseminated tumor cells (DTC) in bone marrow is an important constraint for clinical decision making. Here, we investigated the implications of two different subpopulations of these cells in gastric cancer (GC). Methods GC patients (n = 228) who underwent elective gastric resections were prospectively examined for CTC/DTC. The cells obtained from peripheral blood and bone marrow aspirates were sorted by flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In human GC, the mechanism responsible for maintaining malignant stem cells in the tumor microenvironment is largely unknown [47][48][49][50]. Among the stem cell populations in the stomach, the cells that may be targeted and transformed into tumor initiation cells during chronic Helicobacter pylori infection are those labeled by receptors on the surface of differentiated cluster 44 (CD44) cells [51].…”
Section: Discussionmentioning
confidence: 99%
“…In human GC, the mechanism responsible for maintaining malignant stem cells in the tumor microenvironment is largely unknown [47][48][49][50]. Among the stem cell populations in the stomach, the cells that may be targeted and transformed into tumor initiation cells during chronic Helicobacter pylori infection are those labeled by receptors on the surface of differentiated cluster 44 (CD44) cells [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, CD44 epithelial isoform has been found to be negatively correlated with lymphatic invasion and metastasis of colorectal cancer based on the statistical analysis of a total of 494 colorectal tumor samples [34]. Besides, numerous studies suggest that CD44 can be a promising predictor for clinical outcomes among cancer population, including gastric cancer [45,46], colorectal cancer [34], neuroblastoma [31], myxofibrosarcoma [47], glioma [21], endometrial cancer [40] and osteosarcoma [48]. According to survival analysis, grade II/III glioma patients with high mRNA expression of CD44 experienced poor overall survival (OS) and progression-free survival (PFS) in comparison with low mRNA level of CD44 in an independent manner [21].…”
Section: Open Accessmentioning
confidence: 99%
“…It has been shown that TEVs carrying MMPs may remodel ECM [described in detail in [ 74 , 75 , 76 ] by downregulating E-cadherin expression, degrading ECM components, and upregulating MMP-9, which, all together, facilitated tumor dissemination [ 69 ]. Others observed that TEVs-delivered HA induced motility of CD44 + CAFs and cancer cells [reviewed in [ 77 ], and that CD44 + tumor cells present in the blood [ 77 , 78 , 79 ] exhibited characteristics of cancer stem cells. Expression of this receptor on these cells might results in their dissemination into niches (organotropism) that might be possibly prepared by HA-coated TEVs (see below).…”
Section: Emt and The Role Of Cd44 And Tevsmentioning
confidence: 99%